Experimental and DFT investigation of LiFePO₄/graphene composites prepared via shear exfoliation route - Amun Amri; Mawaddah Mawaddah; Alfatlian Alfatlian; Sunarno Sunarno; Fri Murdiya; Mazhibayev Assylzhan; Khairulazhar Jumbri; Mohammednoor Altarawneh; Chun-Chen Yang; Sulistyo Saputro; M Mahbubur Rahman (International Journal of Renewable Energy Development, 2026)
The performance of LiFePO₄ (LFP) cathodes was successfully enhanced by incorporating two types of graphene obtained through green and low-cost liquid shear exfoliation processes. Commercial LFP was combined with few-layer graphene (FLG) and very few-layer graphene (VFLG), with compositions ranging from 0-4 wt.%. LFP, LFP/FLG, and LFP/VFLG, were characterized using electrochemical impedance spectroscopy (EIS), charge–discharge (CD), XRD, FTIR, and FESEM–EDX. Density functional theory (DFT) calculations were further employed to probe the electronic structure of LFP and an idealized LFP(001)/pristine-graphene interface as a baseline model for interfacial electronic coupling. DFT indicated interfacial charge redistribution and the emergence of C-2p π-derived states near the Fermi level, resulting in bandgap narrowing relative to pristine LFP and suggesting an additional electronic percolation pathway at the interface. Experimentally, EIS showed that VFLG reduced charge-transfer resistance and increased effective electrochemical conductivity, while FLG addition was associated with improved interfacial charge-transfer behavior inferred from EIS. CD tests at 0.5 C showed that the 4 wt.% FLG and 4 wt.% VFLG electrodes delivered the highest specific capacities of 29.98 mAh/g and 44.66 mAh/g, corresponding to increases of 81.9% and 170.5% compared to bare LFP. XRD and FTIR confirmed that LFP phase integrity was maintained, and FESEM–EDX revealed a uniform particle distribution with well-dispersed graphene networks. Overall, these results demonstrated that shear-exfoliated graphene effectively improved electronic connectivity and charge-transfer behavior in LFP cathodes, supported by consistent electrochemical measurements and electronic-structure insights from DFT.